QUEST FOR REDEMPTION IN KHALED HOSSEINI’S ‘THE KITE RUNNER’ - N. Nagapushpam (International Conference on Social and Islamic Studies, 2021)
Khaled Hosseini, Afghan born American novelist who was known for his vivid depictions of Afghanistan, most notably in The Kite runner. Hosseini’s very fond memories of his childhood in peaceful pre-Soviet era Afghanistan, as well as his personal experiences with Afghanistan’s Hazara people led to the writing of his first novel, The Kite Runner. Amir’s quest to redeem himself makes up the heart of the novel. Early on, Amir strives to redeem himself in Baba’s eyes, and he feels responsible for that. To redeem himself to Baba, Amir thinks that he must win the kite tournament and bring Baba the losing kite, both of which are inciting incidents that set the rest of the novel in motion. The more substantial part of Amir’s quest for redemption, however, stems from his guilt regarding Hassan. The guilt drives the climactic events of the story, including Amir’s journey to Kabul to find Sohrab and his confrontation with Assef. The moral standard that Amir must meet his redemption is set early in the book when Baba says that a boy who doesn’t stand up for himself becomes a man who can’t stand up to anything. As a boy, Amir fails to stand up for himself. As an adult, he can only redeem himself, by proving he has the courage to stand up for what is right.